Effect of monolayer graphene on the performance of near-field radiative thermal rectifier between doped silicon and vanadium dioxide. (July 2020) - Zhang, Ping; Yang, Peipei; Zheng, Zhiheng; Yu, Wei
Highlights: The near-field radiative thermal rectifier composed of n -type doped silicon, vanadium dioxide, and graphene is comprehensively investigated. The performance of the near-field radiative thermal rectifier can be significantly affected by the doping concentrations and chemical potential values. The interaction among the surface modes of emitter and receiver modified by graphene and hyperbolic modes of insulating vanadium dioxide is responsible for significantly improving the performance. The total thermal rectification factor of the near-field radiative thermal rectifier can be improved to 7.79 by this interaction. Abstract: We investigate near-field radiative thermal rectifiers (NFRTRs) comprising an asymmetric nanostructure with and without graphene coatings. The asymmetric nanostructure consists of n -type doped silicon (D-Si) and vanadium dioxide (VO2 ) plates separated by a vacuum gap. On the basis of the stochastic Maxwell equations and fluctuation-dissipation theorem, we analyse the effect of graphene on the near-field radiative heat transfer (NFRHT) and the performance of the NFRTR. We find that the total thermal rectification factor (TTRF) of an NFRTR composed of n -type D-Si and VO2 plates can be significantly enhanced by the presence of graphene, depending on the doping concentration of Si, the chemical potential value of the graphene, and the vacuum gap. When both n -type D-Si and VO2 plates are covered by a layer of graphene, the TTRF of the NFRTR whose n -type D-Si and VO2 plates are separated by a 10 nm vacuum gap improves from 4.38 to 7.79 for a doping concentration of 10 19  cm −3 and a chemical potential of 0.25 eV. We attribute this to the strong interaction among the p- polarized surface modes of graphene-covered n -type D-Si with the doping concentration of 10 19  cm −3, p- polarized surface modes of graphene-covered insulating VO2, and p- polarized hyperbolic modes (HMs) of insulating VO2 . This work is important for near-field radiative thermal management and the application of NFRHT-based thermal devices.